Active bacteriophage biocontrol and therapy on sub-millimeter scales towards removal of unwanted bacteria from foods and microbiomes - Stephen T. Abedon (AIMS Microbiology, 2017)
Bacteriophages can be used as antibacterial agents as a form of biological control, e.g., such as phage therapy. With active treatment, phages must “actively” produce new virions, in situ, to attain “inundative” densities, i.e., sufficient titers to eradicate bacteria over reasonable timeframes. Passive treatment, by contrast, can be accomplished using phages that are bactericidal but incapable of generating new phage virions in situ during their interaction with target bacteria. These ideas of active versus passive treatment come from theoretical considerations of phage therapy pharmacology, particularly as developed in terms of phage application to well-mixed cultures consisting of physically unassociated bacteria. Here I extend these concepts to bacteria which instead are physically associated. These are bacteria as found making up cellular arrangements or bacterial microcolonies—collectively, clonal bacterial “clumps”. I consider circumstances where active phage replication would be required to effect desired levels of bacterial clearance, but populations of bacteria nevertheless are insufficiently prevalent to support phage replication to bacteria-inundative densities across environments. Clumped bacteria, however, may still support active treatment at more local, i.e., sub-millimeter, within-clump spatial scales, and potential consequences of this are explored mathematically. Application is to the post-harvest biocontrol of foodborne pathogens, and potentially also to precise microbiome editing. Adequate infection performance by phages in terms of timely burst sizes, that is, other than just adsorption rates and bactericidal activity, thus could be important for treatment effectiveness even if bacterial densities overall are insufficient to support active treatment across environments. Poor phage replication during treatment of even low bacterial numbers, such as given food refrigeration during treatment, consequently could be problematic to biocontrol success. In practical terms, this means that the characterization of phages for such purposes should include their potential to generate new virions under realistic in situ conditions across a diversity of potential bacterial targets.